2021
DOI: 10.1021/acsaem.0c02857
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic SO3 Decomposition Activity of SiO2-Supported Alkaline Earth Vanadates for Solar Thermochemical Water Splitting Cycles

Abstract: Alkaline earth vanadates (Ae–V: Ae = Ca, Sr, and Ba) were supported on mesoporous SiO2 by a wet impregnation method. The catalytic activity of the prepared materials for the decomposition of SO3 into SO2 and O2, which is a key step in solar thermochemical water splitting cycles, was investigated. In the temperature range 700–800 °C, the Ae–V/SiO2 catalysts exhibited remarkably high activities, which were superior to those of supported Pt catalysts in a wide range of weight hourly space velocities (55–220 g-H2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…This indicated that the N SO2 values mostly originated from the desorption of SO 2 adsorbates bound to the surfaces. Nevertheless, LaV 3 O 9 and V 2 O 5 were reported to undergo dissociation into monoclinic LaVO 4 /V 2 O 5 and melting, respectively, at ≥650–700 °C. , These in turn might induce reconstruction of the SO Z 2– -modified LaV 3 O 9 /V 2 O 5 surfaces along with the evolution of novel surface phases including SO Z 2– during the SO 2 desorption step at 650–1000 °C, thus rendering comparison of the N SO2 values of the catalysts hardly convincing.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the N SO2 values mostly originated from the desorption of SO 2 adsorbates bound to the surfaces. Nevertheless, LaV 3 O 9 and V 2 O 5 were reported to undergo dissociation into monoclinic LaVO 4 /V 2 O 5 and melting, respectively, at ≥650–700 °C. , These in turn might induce reconstruction of the SO Z 2– -modified LaV 3 O 9 /V 2 O 5 surfaces along with the evolution of novel surface phases including SO Z 2– during the SO 2 desorption step at 650–1000 °C, thus rendering comparison of the N SO2 values of the catalysts hardly convincing.…”
Section: Resultsmentioning
confidence: 99%
“…31 The sulfur-iodine (S-I) thermochemical water-splitting cycle is widely considered one of the potential mass production ways to produce hydrogen in an efficient, cost-effective and environment-friendly manner. 23,[32][33][34][35][36] The S-I cycle was originally proposed by General Atomics Co. (GA) in the mid-1970s and it is composed of the following chemical reactions: [37][38][39][40][41][42][43][44]…”
Section: Introductionmentioning
confidence: 99%
“…31 The sulfur–iodine (S–I) thermochemical water-splitting cycle is widely considered one of the potential mass production ways to produce hydrogen in an efficient, cost-effective and environment-friendly manner. 23,32–36 The S–I cycle was originally proposed by General Atomics Co. (GA) in the mid-1970s and it is composed of the following chemical reactions: 37–44 H 2 SO 4 → H 2 O + SO 2 + ½O 2 (∼1123 K) Δ H = 186(±3) kJ mol −1 H 2 SO 4 → SO 3 + H 2 O (∼673–773 K) Δ H = 97.54 kJ mol −1 SO 3 → SO 2 + ½O 2 (>1073 K) Δ H = 98.92 kJ mol −1 2HI → H 2 + I 2 (∼473–773 K) Δ H = 12 kJ mol −1 2H 2 O + I 2 + SO 2 → H 2 SO 4 + 2HI (∼373 K) Δ H = −75(±15) kJ mol −1 …”
Section: Introductionmentioning
confidence: 99%
“…Their reactions with SO 3 immediately produce inactive metal sulfates, being more significant at lower reaction temperatures. In a series of preceding studies, 9) 14) we reported that vanadate-based catalysts such as CuV, KV, and CsV oxides supported on mesoporous SiO 2 are potential catalysts for SO 3 decomposition. Their activity at ¯650 °C are among the highest of metal oxide catalysts and are comparable to those of Pt-based catalysts.…”
Section: Introductionmentioning
confidence: 99%